Ryanodol action on calcium sparks in ventricular myocytes - Ramos-Franco, Josefina (2010)
The action of ryanodol on single cardiac ryanodine receptor (RyR2) channels in bilayers and local RyR2-mediated Ca(2+) release events (Ca(2+) sparks) in ventricular myocytes was defined. At the single channel level, ryanodol intermittently modified single channels into a long lived sub-conductance state with an average duration of 3.8±0.2 s. Unlike ryanodine, ryanodol did not change the open probability (Po) of unmodified channels and high concentrations did not promote full channel closure. Ryanodol action was Po dependent with the K(D) varying roughly from 20 to 80 μM as Po changed from ~0.2 to 1, respectively. Ryanodol preferentially bound during long channel openings. In intact and permeabilized rat myocytes, ryanodol evoked trains of sparks at active release sites resulting in a significant increase in overall spark frequency. Ryanodol did not increase the number of active release sites. Long lived Ca(2+) release events were observed but infrequently and ryanodol action was readily reversed upon drug washout. We propose that ryanodol modifies a few channels during a Ca(2+) spark. These modified channels mediate a sustained low intensity Ca(2+) release that repeatedly triggers sparks at the same release site. We conclude that ryanodol is an easily generated reversible probe that can be effectively used to explore RyR2-mediated Ca(2+) release in cells.